(3GdSdGaI GdeSdSdI aj JaGYjd HMQ GdSdSdIs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdaJGM GdhgGH hHYO aEfi CgOi CTQa SdGe ai ZGjI ef PQhI GdJhajQ hGdEMJQGe Edi GdSjO YHO Gdehi Cfg Mjf TQaJge HjQhJfG HGdMVhQ SFdJge Yf JaGYjd HMQ s
(3BNQgG (B:s
(3heYgeG jcf ajgG ef GdYjH ZWg hEf bHd GdCUdGM TF aCUdM hbO LGA Pdc QSGdI cGdebGeI ai gPG GdGSdhH hGdMeO ddg Ydi GdEJeGe hGdJeGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais